Improved arsenite adsorption using iron-impregnated marble dust with surface functionalized by quaternary ammonium ions - Gupta A.D.; Singh H.; Jaiswal V.K.; Goswami M.; Bhadauria V. (My University, 2025)
Abstract: The present study investigates the application of marble dust impregnated with iron and functionalized with quaternary ammonium ions [using ammonium persulphate (APS)] as a novel adsorbent for the removal of arsenite ions from wastewater. The optimal modification parameters were found to be 0.1 M FeCl3, 0.125% NaOH (w/v) and 0.0125 M of APS at a temperature of 80 °C. The maximum uptake capacity of As(III) ions was found to be 50 mg/g with 3.5 g/L of adsorbent for 90 min at pH = 7.0. Maximum negative ∆G° value (− 7.7 kJ/mol) was obtained at 298 K, indicating that low temperature favoured adsorption. Freundlich and Temkin isotherm models gave the best correlation coefficient (R2 > 0.95). The kinetic data were suitably described by pseudo-second-order kinetics. Film diffusion was inferred to be the rate-controlling mechanism based on Boyd plots. The synthesized adsorbent can be regenerated by flushing with an alkaline solution. Graphic Abstract: [Figure not available: see fulltext.]. © 2020, Islamic Azad University (IAU).